Becoming Laura Ingalls Wilder : The Woman behind the Legend - Miller, John E., 1945-2020 (Book collections on Project MUSE., 1998)
Although generations of readers of the Little House books are familiar with Laura Ingalls Wilder's early life up through her first years of marriage to Almanzo Wilder, few know about her adult years. Going beyond previous studies, Becoming Laura Ingalls Wilder focuses upon Wilder's years in Missouri from 1894 to 1957. Utilizing her unpublished autobiography, letters, newspaper stories, and other documentary evidence, John E. Miller fills the gaps in Wilder's autobiographical novels and describes her sixty-three years of living in Mansfield, Missouri. As a result, the process of personal development that culminated in Wilder's writing of the novels that secured her reputation as one of America's most popular children's authors becomes evident. In addition to describing Wilder's apprenticeship as a farm newspaper columnist and occasional magazine writer before she began the production of her novels, Miller discusses Wilder's activities on her family's Rocky Ridge farm and as a vital citizen in Mansfield, Missouri. Playing out her many roles as wife, mother, chicken farmer, churchgoer, bridge player, seamstress, farm loan officer, and political candidate, Wilder led an active life for ninety years.